The Rise of Star Firms : Intangible Capital and Competition - Ayyagari, Meghana; Demirguc-Kunt, Asli; Maksimovic, Vojislav (World Bank, Washington, DC, 2019)
There is a divergence in the returns of top-performing firms and the rest of the economy, especially in industries that rely on a skilled labor force, raising concerns about their market power. This paper shows that the divergence is explained by the mismeasurement of intangible capital. Compared with other firms, star firms produce more per dollar of invested capital, have higher growth, innovation, and productivity and are not differentially affected by exogenous competitive shocks. Their pricing power supports their high intangible capital investment. Some exceptional firms may pose concerns due to their potential to foreclose competition in the future.